DOI: 10.25148/etd.fidc006900
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Terrain-Based Navigation to Enable Persistent Autonomy for Underwater Vehicles in GPS-Denied Environments

Abstract: 2.2 Descriptive statistics for the dataset collected during a mission at the Big Fisherman's Cove, Santa Catalina Island, CA, USA, on July 14th 2016.. 2.3 Descriptive statistics for the dataset collected during a mission at the Lake Nighthorse, CO, USA, on April 25th 2018, in the afternoon.. .. .. .. 2.4 Descriptive statistics for the dataset collected during a mission at the Lake Nighthorse, CO, USA, on May 2nd 2018, in the morning.. .. .. .. . 2.5 Descriptive statistics for the dataset collected during a mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We found that the ATBN framework was reliable for localisation tasks, and could provide pose estimation at accuracies similar to GPS. Further research has been conducted, and for a more detailed analysis of the field trials and corresponding results, we encourage the interested reader to consider [28,29,42].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that the ATBN framework was reliable for localisation tasks, and could provide pose estimation at accuracies similar to GPS. Further research has been conducted, and for a more detailed analysis of the field trials and corresponding results, we encourage the interested reader to consider [28,29,42].…”
Section: Resultsmentioning
confidence: 99%
“…In this section, we present a summary of a few results we have obtained by applying the proposed theory of environmental niche models to the development of ATBN and implementing this onto underwater vehicles during field trials. Complete details of the results presented here can be found in [42].…”
Section: Some Results From the Augmented Terrain‐based Navigation Amentioning
confidence: 99%
See 3 more Smart Citations